Exploring perceptions and awareness of artificial light: A qualitative study among medical and non-medical college students in an urban area of Southern India - Mithra Prasanna; Thapar Rekha; Mallya Ajay; Prabhakar Madhu Malar; Pandey Sonali; Agrawal Yash; Vats Anmol; Agarwal Shreya; Maurya Sarthak; Patel Sneha; Mohanty Marmit; Hooda Divya (Scripta Medica, 2025)
Background/Aim: Exposure to artificial light is linked to increased productivity but may also contribute to sleep disturbances, eye strain and psychological issues. This qualitative study investigated the perceptions and awareness of artificial light among professional college students in Mangalore, Karnataka. Methodology: This qualitative analysis included two focus group discussions (FGD) conducted between April and May 2023. One FGD each was conducted among the second-year medical undergraduate (MBBS) students from the study institute and non-medical students from another Professional College in the urban area of Mangalore. This college was selected using a convenience sampling technique. Two FGDs were held with 20 participants to explore artificial light's benefits and harmful effects in daily life. Results: Participants acknowledged the essential role of artificial light in enhancing productivity, enabling late-night study sessions and facilitating work in poorly lit environments. Comments highlighted that artificial light is integral to modern activities, including cinematography and navigation. However, concerns emerged regarding its adverse effects, including eye strain, headaches, sleep disturbances and potential psychological issues like anxiety and depression. Many noted that excessive exposure to artificial light disrupts circadian rhythms, contributing to insomnia and other health problems. Conclusion: The findings emphasise the need for greater awareness of the implications of artificial light use, promoting healthier practices and informed decisions among students. Educational initiatives and public health strategies should focus on promoting healthier practices and informed decisions to mitigate its risks. Future studies could explore broader sample sizes, diverse demographics and long-term interventions to develop comprehensive measures for balancing artificial light use in daily life.